Fenomena Shrinkflation: Studi Hubungan Antara Penyusutan Kemasan Momogi dengan Kepuasan Pelanggan - Alice, Bernadette; Salsabila, Vina; Nurdayanti, Viona; Fitriayani, Desi; Thufailla, Reghina; Athira, Naila (Universitas Pahlawan Tuanku Tambusai, 2025)
phenomenon of shrinkflation, which is a reduction in product size or content without reducing price, has become a strategy for companies to deal with rising production costs. This research focuses on Momogi products that experienced shrinkflation, where the weight of the packaging was reduced from 14 grams to 5 grams. This study aims to analyze the relationship between product packaging and customer satisfaction and assess the impact of shrinkflation on customer perceptions. The method in this study is associative quantitative used through an online survey with 105 respondents who are loyal customers of Momogi. The results showed that shrinkage of packaging size has a very strong and unidirectional relationship with customer satisfaction. Although shrinkflation does not affect product quality, it does affect perceived customer value, which results in decreased satisfaction and loyalty. In this study, Ha is accepted and Ho is rejected, which means that the hypothesis in this study has a positive influence because the larger the packaging size of a product, the more satisfaction will increase and vice versa, if the product packaging size shrinks, the level of satisfaction will decrease.